The influence of age, length of stay, and gender factors on clean and healthy living behaviors - Zaim, Ryanda Luthfi; Dewata, Indang; Carlo, Nasyfrizal; Umar, Iswandi (COUNS-EDU: The International Journal of Counseling and Education, 2022)
The role of the community is one of the causes of the decline in the quality of drainage water. The decrease in the quality of drainage is related to behavior that is formed based on the characteristics of a person and their environment. The sample in this study is the community from 30 houses directly facing the drainage which is the object of research. The research aims to determine the effect of age, length of stay, and gender on people's behavior in managing household liquid waste and disposing of waste in trash cans. This research was analyzed quantitatively using SPSS, Paired Sample t-test for comparison test. The results of this study showed that the behavior of household wastewater management, age, length of stay, and gender did not have a significant effect. While the behavior of throwing garbage in the trash, only the age factor has a significant effect, while the length of stay and gender factors have no significant effect.